Revitalizing the soul of higher learning - Ujang, Zaini (Penerbit UTM, 2013)
In general, the central gist of the 2013 New Year Address is on the concept of New Academia with the theme ‘Revitalizing the Soul of Higher Learning’. Thus, this book incorporates the concept of knowledge culture, reinstating New Academia and consolidating the Institutional DNA. All these, aim to develop an entrepreneurial based Research University, which is vibrant with scholarly programmes. This book also outlines the transformation agenda with various action plans which will act as guidelines and direction for the academic community. Planning, together with strategic implementation of various initiatives related to the New Academia and Institutional DNA are needed to enable the transformation agenda to become meaningful resulting in multiple impact. In this context, formulation of the Institutional DNA requires “intrinsic” change among the academic community to sharpen the mind and strengthen the might to progress further. A consolidated and high synergy team spirit, support from staff and students of all levels, and synergy with various partners would ultimately result in the manifestation of being propelled forward, thus enabling the implementation of mission and vision to instil the culture of knowledge towards the development of a civilised nation.